Liquid Stratification and Diffusion‐Induced Anisotropic Hydrogel Actuators with Excellent Thermosensitivity and Programmable Functionality - Pengli Dong (Wiley, 2021)
Smart hydrogel actuators with programmable anisotropic structures present fascinating prospects considering their distinctive shape transformation and controllable environmental responsiveness under external stimuli. However, the design of anisotropic hydrogels with simple and universal fabrication and programmable functionality is challenging for their valuable applications in smart actuators and soft robots. Herein, a simple, green, and devisable strategy is proposed to construct a heterogeneous porous hydrogel system by the different liquid diffusion (such as amyl alcohol, water, and ethanol) into a monomeric precursor solution of thermosensitive hydrogels. The well‐defined micro/nanoporous gradient and patterned structures related to selective liquid stratification and interfacial diffusion favor the fast response and accurate programmable deformation of hydrogels under temperature stimuli. Inspiringly, this simple diffusion‐driven tactic can be perfectly applicable for different responsive hydrogels with programmable multifunctionality by adding functional nanomaterials into the diffusible liquid. This green, general, and facile diffusion‐driven strategy provides significant guidance for fabricating environmentally responsive hydrogels with tailorable functionality for their multipurpose applications in drug delivery, bioengineering, smart actuators, and soft robots.